Ocean anatomy ebook The curious parts & pieces of the world under the sea. - Rothman, Julia (Anatomy., 2020)
Take a deep drive into the wonders of the sea with Julia Rothman's bestselling illustrated ocean guide. Follow Rothman’s inquisitive mind and perceptive eye along shorelines, across the open ocean, and below the waves for an artistic exploration of the watery universe. Through her drawings, discover how the world’s oceans formed, why the sea is salty, and the forces behind oceanic phenomena such as rogue waves. Colorful anatomical profiles of sea creatures from crustacean to cetacean, surveys of seafaring vessels and lighthouses, and the impact of plastic and warming water temperatures are just part of this compendium of curiosities that will entertain and educate readers of all ages.  Also available in Julia Rothman's Anatomy series: Nature Anatomy, Farm Anatomy, Food Anatomy, Nature Anatomy Notebook, and Wildlife Anatomy.